Government Communication Strategy in The Establisment of New Aotonomous Regoin in The Papua - Isnaini Varidah Uswanas (PERSPEKTIF, 2023)
The government and the house of representatives of the Republic of Indonesia have approved the establishment of new autonomous regions namely South Papua Province, Central Papua Province, and Papua Mountains Province. The plenary meeting of parliament was set up on 30 July 2022. This establishment of 3 (three) provinces is accommodated in Law Number 2 of 2021 concerning special autonomy for Papua.  Before the law was revised, the authority to form a new autonomous region was proposed by The Papuan People’s Assembly or Majelis Rakyat Papua and The Papuan People’s Representative Council or Dewan Perwakilan Rakyat Papua. This research aims to study the government’s communication strategy in conveying the goals of establishing the new autonomous regions in Papua. This study uses a descriptive analysis approach. Data was collected through interviews with informants involved in the formation of new autonomous regions and Papua community leaders. Secondary data was collected from media publication, official government websites, scientific publication, and reports. Laswell’s communication model is used for the evaluation of the government’s communication strategy. The study recommends that the government’s communication strategy should be more intensive through the ministry of home affairs to local government affected by the establishment new provinces, group communication between government and indigenous group, and interpersonal communication among Papuan’s elites who can influence public perception